HANSKY ALEKSEY PAVLOVITCH - Lemeshchenko, N. D.; Shevchyuk, T. V. (Одеські астрономічні публікації, 2008)
An essay devoted to A.P.Hansky, a famous astronomer, a graduate of Novorossiysk (Odessa) University.